Renal graft intolerance syndrome in late graft failure patients: efficacy and safety of embolization as first‐line treatment compared to surgical removal. (5th March 2017) - Al Badaai, Ghalib; Pernin, Vincent; Garrigue, Valérie; Monnin, Valérie; Murez, Thibaut; Fadli, Saad Ed Dine; Molinari, Nicolas; Thuret, Rodolphe; Iborra, François; Mourad, Georges
Summary: Although renal graft percutaneous embolization was introduced to avoid the risk associated with graft nephrectomy, there is no universal consensus about its indications and results. In order to evaluate the efficacy of graft embolization in the treatment of graft intolerance syndrome as well as its safety compared to surgical removal with respect to complications and other morbidity measures, We performed a retrospective observational study comparing two groups of patients treated for graft intolerance syndrome: Group 1: patients who had embolization as first‐line treatment and Group 2: patients directly treated by surgical removal. 72 patients were included, (32 in Group 1 and 40 in Group 2); the postintervention follow‐up continued for 12 months. Patients in Group 1 are older than those in Group 2. Otherwise, the two groups are similar concerning sex, manifestations of graft intolerance syndrome, diabetes and nutritional and functional status. The overall success rate of embolization in complete resolution of graft intolerance syndrome and ultimately avoidance of surgical removal was 84.37%. The surgical removal group had more serious complications, a longer hospital stay and needed more blood transfusions. We conclude that embolization of symptomatic renal grafts has considerable efficacy with less morbidity, and no serious complications compared to the standard surgical graft removal.